Evaluating the effect of managerial caution on real earnings management - Hemmati, Hasan; Taghizad, Gholamhasan; Mahmoudi, Siavash (Journal of Entrepreneurship, Business and Economics, 2017)
High emphasis on the profit and loss and the net profit has motivated the management to manipulate the company's activities in order to achieve the target profit and consequently created the concept of earnings management. On the other hand, according to uncertainty to reduce the likelihood of losses and better illustrate organizational performance researchers examined a new method as managerial caution.  This issue is more important at the stock exchanges. Therefore, this study aimed to investigate the effect of managerial caution on real earnings management. For this purpose and in order to survey hypotheses after screening, 118 listed companies on the Tehran Stock Exchange (TSE), in the period of 2009 to 2013, were studied. The results showed that there is a significant negative relationship between managerial caution and real earnings management. This means that, in that period, the companies that have benefited from precautions management show less interest to use real earnings management actions and it has shown that using managerial caution leads to reduce the use of earnings management. Research paper Keywords: Managerial caution, Earnings management, Real earnings management Reference to this paper should be made as follows: Hemmati, H., Taghizad, G., & Mahmoudi, S. (2017). Evaluating the effect of managerial caution on real earnings management, Journal of Entrepreneurship, Business and Economics , 5 (2), 127–146.